Tight regulation of memory CD8(+) T cells limits their effectiveness during sustained high viral load - West, Erin E; Youngblood, Ben; Tan, Wendy G; Jin, Hyun-Tak; Araki, Koichi; Alexe, Gabriela; Konieczny, Bogumila T; Calpe, Silvia; Freeman, Gordon J; Terhorst, Cox; Haining, W Nicholas; Ahmed, Rafi (Immunity (Cambridge, Mass.), 2011)
To design successful vaccines for chronic diseases, an understanding of memory CD8(+) T cell responses to persistent antigen restimulation is critical. However, most studies comparing memory and naive cell responses have been performed only in rapidly cleared acute infections. Herein, by comparing the responses of memory and naive CD8(+) T cells to acute and chronic lymphocytic choriomeningitis virus infection, we show that memory cells dominated over naive cells and were protective when present in sufficient numbers to quickly reduce infection. In contrast, when infection was not rapidly reduced, because of high antigen load or persistence, memory cells were quickly lost, unlike naive cells. This loss of memory cells was due to a block in sustaining cell proliferation, selective regulation by the inhibitory receptor 2B4, and increased reliance on CD4(+) T cell help. Thus, emphasizing the importance of designing vaccines that elicit effective CD4(+) T cell help and rapidly control infection.